Evaluation of Color, Hardness, and Tannin Content of Soft Cheese with Biduri Leaf Extract Level - sulmiyati Natsir; Gemini Ermiani M. Malelak (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2022)
Soft cheese Suspesi is a soft cheese to which biduri leaf extract is added as a coagulant. There is no research on the color, hardness, and content of tannins contained in soft cheese suspesi. The purpose of this research was to analyze and evaluate the hardness, color *L, *a, *b, and tannin content with the addition of biduri leaf extract at levels of 3% and 5% in soft cheese suspesi. This research used a completely randomized design with two treatments with six replications. A1= Biduri leaf extract level 3% (v/v), A2= Biduri leaf extract level 5% (v/v). Data on hardness, color, and tannin content were analyzed by Independent T-Test. The results showed a significant difference (P<0.05) in the hardness, color *L, and tannin content. Color *a and color *b did not show a significant difference (P>0.05). In conclusion, the levels of added biduri leaf extract gave different levels of hardness, color *L, *a, *b, and tannin content in the soft cheese suspesi. The characteristics of the soft cheese suspesi increased in terms of hardness, color *L, *a, *b, and tannin content in line with the level of added biduri leaf extract.